Relation Between Eating Behaviours and Personal Body Image Perception of Yasar University Students - Ince Yenilmez, Meltem; Ince Palamutoglu, Merve (International Journal of Contemporary Economics and Administrative Sciences, 2021)
In this study, it is aimed to determine that 554 students, studying at Yasar University, whether they have a predisposition to eating behavior disorder or not. Gender, age, weight and height information have been asked and applied the 26-item Eating Attitudes Test (EAT-26) adapted to the analysis. According to the EAT-26 evaluation scale; who score is "≥30", he is described as "he has a predisposition to eating behavior disorder". The data were evaluated by frequency and Pearson chi-square tests. EAT-26 score was determined as ≥30 in 1.5% (n=5) of women students and in 79.4% (n=16) of men students. According to the EAT- 26 score, 16.2% (n=90) of weak students, 62.8% (n=248) of normal students and 17% (n=94) of before obesity (pre- obese) students have been identified regarding the results. When EAT-26 score was evaluated according the gender of the students, it was seen that 34.3% (n=190) of students are male and 65.7% (n=364) of students are women. Average EAT-26 score of the students was found as 20.36±1.76 and 4% (n=22) of them have eating disorder. But no statistically significant difference was found between the age of participation in the survey according to gender (p>0.05). This will be an advantage for young generations that they will be socially self confident which will not affect their economic situation.